2006
DOI: 10.1182/blood-2006-04-014779
|View full text |Cite
|
Sign up to set email alerts
|

Altered granulopoietic profile and exaggerated acute neutrophilic inflammation in mice with targeted deficiency in the sialyltransferase ST6Gal I

Abstract: Elevation of serum sialic acid and the ST6Gal-1 sialyltransferase is part of the hepatic system inflammatory response, but the contribution of ST6Gal-1 has remained unclear. Hepatic ST6Gal-1 elevation is mediated by P1, 1 of 6 promoters regulating the ST6Gal1 gene. We report that the P1-ablated mouse, Siat1⌬P1, and a globally ST6Gal-1-deficient mouse had significantly increased peritoneal leukocytosis after intraperitoneal challenge with thioglycollate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
90
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(95 citation statements)
references
References 59 publications
4
90
0
Order By: Relevance
“…Thus, Siat1⌬P1 mice might lack the particular subset of B cells that produce sialylated Fc glycans. Indeed, circulatory ST6Gal-1 deficiency has been attributed to altered hematopoietic activity in bone marrow (11,12,16). IgG acquires antiinflammatory properties upon Fc sialylation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, Siat1⌬P1 mice might lack the particular subset of B cells that produce sialylated Fc glycans. Indeed, circulatory ST6Gal-1 deficiency has been attributed to altered hematopoietic activity in bone marrow (11,12,16). IgG acquires antiinflammatory properties upon Fc sialylation.…”
Section: Discussionmentioning
confidence: 99%
“…Our laboratory has demonstrated that ST6Gal-1 deficiency results in a generally proinflammatory state; mice with genetically induced ST6Gal-1 deficiency exhibit exaggerated acute peritonitis and Th2 pulmonary inflammation (11,12). This phenotype was attributed specifically to the inactivation of the liver-specific promoter P1, one of six promoters regulating tissue-and cell-specific transcription of the ST6Gal-1 gene (13)(14)(15).…”
Section: Large-dose Intravenous Immunoglobulin (Ivig)mentioning
confidence: 99%
“…The humoral response (28 -30), maintenance of myeloid homeostatic balance (22), modulation of dendritic cell activity (31), T cell functionality (32), and integrin signaling (33)(34)(35) are but a few physiologic processes with implicated ST6Gal-1 participation. The idea of ST6Gal-1 pleiotropy Expression of (top left) total ST6Gal-1 mRNA, (top right) P1-transcribedST6Gal-1 mRNA that contains the unique Exon H sequence (2), and (bottom) selected hepatic sialyltransferases were measured by real-time PCR relative to the expression of RPL32, a ribosomal protein, as a reference standard.…”
Section: Discussionmentioning
confidence: 99%
“…poiesis, as mice with a specific ablation to the P1 region had excessive neutrophilic and eosinophilic inflammatory responses (22,23). Siat1⌬P1 animals had the identical degree of excessive inflammation as Siat1-null animals that were completely devoid of ST6Gal-1, indicating only the P1-mediated pool of ST6Gal-1 was important for myelopoietic regulation.…”
mentioning
confidence: 95%
See 1 more Smart Citation